Association of Pre-treatment Sarcopenia with Side Effects and Prognosis in Non-small Cell Lung Cancer Patients Receiving Erlotinib - DEMİRCAN, NAZIM CAN; ENGÜR, CEREN ÖZGE; AKIN TELLİ, TUĞBA; BAŞOĞLU TÜYLÜ, TUĞBA; ARIKAN, RUKİYE; ÖZGÜVEN, SALİH; DANE, FAYSAL; KAYA, HANDAN; ÖNEŞ, TUNÇ; YUMUK, PERRAN FULDEN (My University, 2022)
OBJECTIVE We investigated the relationship of baseline sarcopenia with toxicities, treatment response, and survival in patients who had non-small cell lung cancer (NSCLC) harboring an epidermal growth factor receptor (EGFR) mutation and received erlotinib.METHODS Computed tomography images from PET/CT scans before erlotinib treatment were retrospectively assessed. Skeletal muscle index, calculated as skeletal muscle area at third lumbar vertebra level/square of height, was used to define sarcopenia with < 52.4 cm2/m2 for males and < 38.5 cm2/m2 for females. Cox hazard models were conducted to determine predictors of survival.RESULTS The study included 30 patients, and 11 (36.7%) were sarcopenic. All-grade and Grade 3 toxicities were more frequent in sarcopenic group, although it was statistically insignificant (81.8% vs. 63.2%, p=0.282 for all-grade, and 18.2% vs. 10.5%, p=0.552 for grade 3). Response rates were 63.6% in sarcopenic and 68.4% in non-sarcopenic patients (p=0.789). Median progression-free survival was 7.9 and 9.2 months in sarcopenic and non-sarcopenic cases, respectively (p=0.561). However, median overall survival (OS) of sarcopenic patients was significantly shorter than non-sarcopenic ones (11.8 vs. 30.2 months, p=0.023), and sarcopenia predicted OS independently in multivariate analysis (Hazard ratio=2.63, p=0.029).CONCLUSION Early recognition, treatment, and prevention of sarcopenia may improve long-term survival in EGFRmutant NSCLC patients treated with first-line erlotinib.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Onkoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Oncology; Health Sciences; ONKOLOJİ; Klinik Tıp; Klinik Tıp (MED); ONCOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Epidermal growth factor receptor; erlotinib; non-small cell lung cancer; prognosis; sarcopenia; BODY-MASS INDEX; 1ST-LINE TREATMENT; SOLID TUMORS; OPEN-LABEL; CHEMOTHERAPY; TOXICITY; MULTICENTER; DETERMINANT; PREVALENCE; Epidermal growth factor receptor; erlotinib; non-small cell lung cancer; prognosis; sarcopenia